Pengembangan Sistem Klasifikasi Tipe Kepribadian Siswa Secara Psikologis dengan Algoritma Decision Tree C.45 - Nuraini, Rini; Al Hakim, Rosyid Ridlo; Lisnawati, Tuti; Fariati, Wieke Tsanya (Forum Kerjasama Pendidikan Tinggi, 2021)
In the world of education knowing the personality type of students is very important. This is because a person's personality is influential in his learning activities and how he digests and captures the material presented by the teacher. For this reason, knowing the classification of students' personalities needs to be identified so that teachers or students themselves can optimize self-change in a better and positive direction. This study aims to develop a psychological classification system for student personality types using the C.45 decision tree algorithm. The personality type used as a class in the classification is based on psychology, including: Sanguine, Phlegmatic, Choleric and Melancholic. In this study, a web-based system was developed, so that it is easy to use for teachers and students to recognize the personality of these students. To determine the personality of students psychologically, students answer questions in the system, then the system will classify based on the answers from these students. The C.45 decision tree algorithm serves to find knowledge or patterns of characteristic similarity in a particular group or class. From the test results, the pecision value is 90%, the recall is 85% and the accuracy is 88%. This shows that the C.45 decision tree algorithm can perform personality type classification well